Isolasi dan Uji Antimikroba Substansi Bioaktif Mikroba Endofit Ranting Tanaman Johar (Cassia siamea Lamk.) - Shirly Kumala; Syarmalina Syarmalina; Atut Ruswita Handayani (JURNAL ILMU KEFARMASIAN INDONESIA, 2006)
Assay for secondary metabolite of endophytic fungi from Cassia siamea Lamk.. (Johar Plant) has been investigated. Endophyitic fungi are microorganisms that live asymtomatically within the living tissue of host plants. Endophytic fungi associate with plant, they can help the metabolism of host plant and produce potensial secondary metabolite. The purpose of this experiment were to investigate endophytic microbial agents. Isolate of endophytic fungi from twig of Cassia siamea Lamk., using direct seed method was carried out. The microbial activity was carried out with dilution method using paper disk and glass cylinder. The results showed 3 isolates of bacteria and 7 isolates of endophtyic fungi. The metabolite from three isolates of bacteria had the anti-microbial activity more poten toward Gram positive than Gram negative and four isolates of fungi had anti-Aspergillus agent.